2005
DOI: 10.1111/j.1743-6109.2005.20233.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Specific Antigen in Patients with Hypogonadism: Effect of Testosterone Replacement

Abstract: Introduction The effect of parenteral testosterone replacement therapy on prostatic specific antigen (PSA) level or the development or growth of prostate cancer is unclear. Aim To assess the effect of testosterone replacement on PSA level in patients with hypogonadism associated with erectile dysfunction (ED). Methods A total of 187 male patients above the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
2
16
2
1
Order By: Relevance
“…283,284 Men successfully treated for prostate cancer and diagnosed with hypogonadism are candidates for testosterone replacement after a prudent interval if there is no clinical or laboratory evidence of residual cancer. 285,286 In addition, no effect was found of testosterone replacement therapy on PSA levels [287][288][289] and the change in PSA were not influenced by the mode of testosterone replacement therapy, patient age, or baseline levels of PSA or testosterone. 290 The online prostate cancer risk calculator is one of the most commonly used tools to assist the clinician in assessing the risk of prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 93%
“…283,284 Men successfully treated for prostate cancer and diagnosed with hypogonadism are candidates for testosterone replacement after a prudent interval if there is no clinical or laboratory evidence of residual cancer. 285,286 In addition, no effect was found of testosterone replacement therapy on PSA levels [287][288][289] and the change in PSA were not influenced by the mode of testosterone replacement therapy, patient age, or baseline levels of PSA or testosterone. 290 The online prostate cancer risk calculator is one of the most commonly used tools to assist the clinician in assessing the risk of prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 93%
“…All of the men met inclusion criteria, with a PSA level o4.0 ng ml À1 before treatment, normal results on DRE, or a pretreatment prostate biopsy negative for cancer for men with an abnormal DRE or an elevated PSA level. PSA levels increased, but no cancers were detected in the El-Sakka et al 41 1-year study of patients with hypogonadism associated with erectile dysfunction. Douglas et al…”
mentioning
confidence: 92%
“…Based on a study of 65 men Gustafsson et al also observed that there was no relationship between PSA and Testosterone [7]. El-Sakka AI et al in 2005 studied the effect of Testosterone replacement on PSA level in 187 hypogonadal men for one year [8]. There was no significant association found between PSA level and the duration of Testosterone replacement therapy in their study population.…”
Section: Discussionmentioning
confidence: 89%